NILAI-NILAI DALAM CERITA RAKYAT LEGENDA SAWERI GADI DI DESA UP KOTA WUNA KECAMATAN TONGKUNO KABUPATEN MUNA - Non - Abdin (Cakrawala Listra: Jurnal Kajian Sastra, Bahasa, dan Budaya Indonesia, 2018)
Abstract: This research aims to describe: (1) The structure of Folklore "Saweri Gadi" in the village of UP State Wuna Tongkuno District of Muna. (2) Values ​​of Folklore "Saweri Gadi" in the village of UP State Wuna Tongkuno District of Muna. This research method is descriptive qualitative with using this type of field research. Data and data sources used are sources or informants. Data collection techniques used were depth interview (in-deth interview) and obserfasi, and content a’//;nalysis techniques were used that approach to structural analysis. The results of this study, namely the structure of folklore "Saweri Gadi" the theme of the struggle of the people to survive being stranded in a region, and the grooves contained in folklore "Saweri Gadi" is the advanced groove. Background consists of a place, time and social. Characters and characterizations in folklore is distinguished above figure is based on its role in the story. So that the values ​​in folklore is comprised of religious values, social values, moral values ​​and cultural values. Key word: Values ​​in Folklore Legend Saweri Gadi